Geogrid‐Inspired Nanostructure to Reinforce a CuxZnySnzS Nanowall Electrode for High‐Stability Electrochemical Energy Conversion Devices. Issue 12 (2nd February 2017) - Chiu, Jian‐Ming; Chen, E‐Ming; Lee, Chuan‐Pei; Shown, Indrajit; Tunuguntla, Venkatesh; Chou, Jui‐Sheng; Chen, Li‐Chyong; Chen, Kuei‐Hsien; Tai, Yian
Abstract : Inspired by geogrids commonly applied in construction engineering to reinforce side slopes and retaining walls, the use of a "nano‐geogrid" to reinforce a Cu x Zn y Sn z S (CZTS) nanowall electrode for application in electrochemical reactions is demonstrated. The CZTS nanowall electrode reinforced by the nano‐geogrid (denoted as NWD) shows not only remarkable mechanical and electrochemical stability but also considerable electrochemical performances. The NWD demonstrated as a counter electrode in a dye‐sensitized solar cell shows a power conversion efficiency of 7.44 ± 0.04%, comparable with the device using Pt as electrode, and also significantly improves device stability as compared with that afforded by an electrode comprising a CZTS nanowall without the nano‐geogrid (denoted as NOD). In addition, applying the NWD electrode as a cathode in photo‐electrochemical hydrogen evolution reactions (HERs) yields a photocurrent density of −10 mA cm −2 at −0.162 V (vs RHE) under AM 1.5 illumination. Moreover, when HERs are conducted under extreme conditions, the NWD electrode remains intact, whereas the NOD electrode is completely peeled off after 10 min of reaction. Therefore, the concept of using a mimetic rational nanostructure could pave the way for the possibility of improving the performance and stability of various devices. Abstract : Inspired by geogrids commonly applied in construction engineering to reinforce side slopes and retaining walls, the use of a "nano‐geogrid" to reinforce a Cu x Zn y Sn z S nanowall electrode for high stable electrochemical applications is demonstrated.